Clinical Dental Hygienists' Awareness of the Medical Technicians Act and Clinical Performance in Korea - Song-I Back; Ji-Hyun Min (The Korean Society of Dental Hygiene Science, 2020)
Background: In Korea, laws for many medical technicians were revised in the Enforcement Decree of the Medical Technicians Act (MTA), which was announced on December 2018, whereas those related to dental hygienists remained unchanged. This study aimed to determine the awareness and opinions of dental hygienists regarding MTA.Methods: Dental hygienist were recruited as participants via convenient sampling in Seoul, Gyeonggi-do, and Chungcheong-do; data from 291 self-reported questionnaire responses were used for the final analysis. We investigated the participants' general characteristics, awareness, and request for the amendment of the MTA. The compliance with the work scope specified in the MTA and level of demand for revision of the MTA were analyzed by independent t-test and one-way analysis of variance. For all statistical analyses, the significance level was set at 0.05.Results: For the 2018 MTA revision, 99 (34.02%) knew that dental treatment assistance and surgery assistance were excluded, whereas 192 (65.98%) did not know. The item "The current medical technician law must be revised" was scored 4.13±0.80 out of 5 points, and significant differences were identified according to the education level, career, and position (p＜0.05). The item "It is necessary to institutionalize the expanded work scope beyond the work scope of dental hygienists specified in the MTA" was scored 4.02±1.04 out of 5 points, and significant differences were identified according to age (p＜0.05).Conclusion: The participants wanted the MTA to be revised to reflect the real-world work performed by dental hygienists in the dental clinical field. The legal system must ensure the legal protection of the work area of the dental hygienist as an oral health professional, and recognize the legal work scope of the dental hygienist.